A prison based nurse‐led specialist diabetes service for detained individuals. Issue 2 (July 2014) - Mills, Lesley
Abstract This study aimed to examine whether providing a nurse‐led specialist diabetes service within the prison setting can improve the management of diabetes by reducing HbA1c – thus reducing hospital admissions for hypoglycaemia and diabetic ketoacidosis and, in turn, reducing UK National Health Service costs. Monthly nurse‐led clinics were carried out to review prisoners' diabetes management and control. The study prospectively monitored the care of diabetic men serving a prison sentence in a large English prison during a 12‐month period within a specialist nurse‐led diabetes clinic, and compared the outcomes to the previous 12 months before the clinic was set up. The study subjects comprised 27 male prisoners – of whom 37% have type 1 diabetes and 63% have type 2 diabetes – all detained in one prison, HM Prison Risley, in the north west of England. Main outcome measures were: reduction in hospital and accident and emergency (A&E) admissions; reduction in the rate of failed attendance at hospital outpatient clinic appointments ('did not attend') and in the rate of cancelled consultant outpatient clinic appointments; and improvement in diabetes management and control. The results showed that hospital admission rates reduced, with only two admissions in 12 months. One was due to hypoglycaemia (overdose) and one due to infection. There were no admissions for diabetic ketoacidosis. Baseline HbA1c was 74mmol/mol (8.9%); range 39–108mmol/mol (5.7–12.0%). At one‐year follow up, HbA1c had decreased to 58mmol/mol (7.5%); range 56–119mmol/mol (7.3–13.0%). The number of episodes of severe hypoglycaemia in the preceding 12 months was greatly reduced from 17 to 1 (p<0.001). It was concluded that prisoners should be offered care that meets national standards. They should have access to medication and education to help manage their diabetes. Commissioning of services for prisoners with diabetes needs to be addressed if this has not already been done. A comprehensive approach to the care of people with diabetes can be an effective way in which to improve overall health and prevent acute/chronic complications. Providing a prison based nurse‐led specialist diabetes service within a prison can reduce hospital admissions, reduce the number of hospital outpatient clinic appointments, improve patient outcomes and ultimately save the UK National Health Service a substantial amount of money. Eur Diabetes Nursing 2014; 11(2): 53–57